PENGARUH KESADARAN WP, KUALITAS PELAYANAN, DAN SANKSI PERPAJAKAN PADA KEPATUHAN WP AIR TANAH - Santika, Kadek Adi (E-Jurnal Akuntansi; Vol 12 No 3 (2015), 2015)
Tax is one source of revenue to finance national development. One way to increase government revenue from the tax sector is to increase taxpayer compliance itself. This study was conducted to see the effect of taxpayer awareness, quality of service, and tax penalties on taxpayer compliance groundwater in Denpasar City Revenue Service. 90 samples are obtained based on the formula Slovin. The data analysis technique used is descriptive statistics and multiple linear regression analysis was preceded by the classical assumption. Based on the results of the analysis are used to denote the taxpayer awareness, quality of service, and tax penalties effect on taxpayer compliance groundwater in the Department of Revenue of Denpasar with tcount each variable is greater than ttable is 1.658, and the significance value greater than 0, 05.
Keywords: Taxpayer Awareness, Quality Service, Tax Penalties, Taxpayer Compliance Groundwater